Developing meaningful water-energy-food-environment (WEFE) nexus indicators with stakeholders: An Upper White Nile case study - Schlemm, Annika; Mulligan, Mark; Tang, Ting; Agramont, Afnan; Namugize, Jean; Malambala, Enos; van Griensven, Ann (The Science of the total environment, 2024)
The Upper White Nile (UWN) basin plays a critical role in supporting essential ecosystem services and the livelihoods of millions of people in East Africa. The basin has been exposed to tremendous environmental pressures following high population growth, urbanisation, and land use change, all of which are compounded by the threats posed by climate change and insufficient financial and human resources. The water-energy-food-environment (WEFE) nexus provides a framework to assess solution options towards sustainable development by minimising the trade-offs between water, energy, and food resources. However, the majority of existing WEFE nexus indicators and tools tend to be developed without consideration of practitioners at the local level, thus constraining the practical application within real-world contexts. To try to address this gap and operationalise the WEFE nexus, we examined how local stakeholders frame the most pressing WEFE nexus challenges within the UWN basin, how these can be represented as indicators, and how existing WEFE nexus modelling tools could address this. The findings highlight the importance of declining water quality and aquatic ecosystem health as a result of deforestation and increasing agricultural intensity, with stakeholders expressing concerns for the uncertain impacts from climate change. Furthermore, a review of current WEFE nexus modelling tools reveals how they tend to be insufficient in addressing the most pressing environmental challenges within the basin, with a significant gap regarding the inclusion of water quality and aquatic ecosystem indicators. Subsequently, these findings are combined in order to guide the development of WEFE nexus indicators that have the potential to spatially model the trade-offs within the WEFE nexus in the UWN basin under climate change scenarios. This work provides an example of how incorporating local stakeholder's values and concerns can contribute to the development of meaningful indicators, that are fit-for-purpose and respond to the actual local needs. [Display omitted] •East Africa is faced with many water-energy-food-environment (WEFE) nexus challenges.•Stakeholders' interviews identified water quality and aquatic ecosystem challenges.•Existing WEF nexus tool is insufficient in addressing these challenges.•Novel WEFE indicators developed ensures that future research is fit-for-purpose.